Gastrointestinal fistula endoscopic closure techniques - Bhurwal, Abhishek (Ann Gastroenterol, 2020)
With the improvement in flexible endoscopic technology and the availability of new endoscopic devices, current endoscopic therapies spare many patients who would otherwise undergo surgical repair of gastrointestinal fistulas. These endoscopic techniques include gastrointestinal stents, endoscopic suturing, cardiac septal occluders, endo-sponge, vacuum therapy and others. This review elaborates on the indications, evidence, procedural details, efficacy, and complications of various endoscopic techniques for the management of gastrointestinal fistulas.